Improving Safety & Ride Comfort through Dual Suspension System in Road Vehicles - Kumar, Chandar; Arain, Zahid Ali; Raza, Syed Ahmed; Kumar, Suresh; ul Abedin Abidi, Syed Zain; Lal, Chaman (International Journal of Engineering and Management Sciences, 2020)
The essential objective of the proposed suspension framework is to limit the undesired disturbance of a vehicle because of uneven surfaces on streets. This framework in vehicles is comprise of some fundamental components like dampers and springs which ingests the stuns that are instigated by unusual streets. In any case, these frameworks can just work up to a predefined constrain. Vehicle suspension frameworks are planned by taking the solace capacity of a traveler in record and to enhance the street grasp on each surface. This examination proposes an idea for structuring a superior suspension arrangement of vehicles to upgrade the nature of the drive without corrupting the dependability of the vehicle plan. In this exploration, a mix of two suspension framework is presented in which one goes about as an essential suspension while different fills in as an optional framework that can adequately lessen the vibrations. This mix upgrades the customary framework that is right now introduced in vehicles without bargaining on solace and street hold.